A comparison of imaging techniques to measure skin flap thickness in cochlear implant patients to enable pre-operative device selection. (4th July 2022) - Rees, Jacob; Abrar, Rohma; Stapleton, Emma
Abstract : Objectives: Magnetic resonance imaging (MRI)-compatible cochlear implants have weaker internal magnets than non-MRI-compatible devices. Their suitability for individual patients is limited by skin flap thickness, traditionally measured with a needle in the operating theatre. We aimed to establish the accuracy of imaging modalities to measure skin flap thickness pre-operatively, with the goal of streamlining device selection and simplifying the consent process. Methods: Skin flap measurements were taken using ultrasound (US), computed tomography (CT) and MRI and compared for agreement with intra-operative needle measurement. Results: Twenty-seven skin flaps were included. Absolute agreement between needle and imaging methods was low: needle/US: 44.4% (95% confidence interval [CI]: 27.7–62.7), needle/CT: 39.1% (95% CI: 22.2–59.2), needle/MRI: 20.8% (95% CI: 9.2–40.5). However, US and CT showed 95.7% agreement (95% CI: 76.0–99.8) with intraclass correlation of 0.996 (95% CI: 0.991–0.998) and narrow Bland–Altman limits of agreement (−0.37, 0.45 mm). BMI and skin flap thickness showed a significant positive correlation ( rs = 0.664, P = 0.002) but no significant correlation was observed for age (P = 0.659). Discussion: The high level of agreement between US and CT suggests that there are more accurate measurements of skin flap thickness compared with needle or MRI. Needle measurements are consistently smaller. Conclusion: The use of CT or US should be considered when making pre-operative device choices.